Perbandingan Konsep Esensi dan Eksistensi dalam Pemikiran Metafisika Islam: Perspektif Ibnu 'Arabi dan Mulla Sadra - Manggala, Kayan; Soleh, Achmad Khudori; Syihabuddin, Muhammad; Wafi, Hasan Abdul (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
The concept of wahdah al-wujud Ibn Arabi (1165-1240 AD) and the concept of Al-Hikmah Al-Muta'aliyah Mulla Sadra (1571-1640 AD) are the most important contributing concepts in metaphysical thought in Islam. Hence, it is also important to understand these two concepts to study both the concept of essence and existence as a basis for understanding. The purpose of this study has objectives, namely (1) to know the concept of essence and existence from the perspective of Ibn Arabi. (2) to know the concept of essence and existence of Mulla Sadra's perspective. (3) to know the meeting point and the point of difference in the concept of essence and existence of both. The method used to explore this literature study by examining the work of the two figures, namely Ibn Arabi's work entitled “Futûhât al-Makkiyah” with Mulla Sadra's work entitled “Al-Asfar al-Arbaà” as a primary source and several related articles relevant to the topic discussed with qualitative descriptive analysis. The results of this study are three, namely (1) according to Ibn Arabi (1165-1240 AD), existence is the form of essence, so that existence precedes essence. So, if something has existence then something has essence. But the opposite also applies. (2) According to Mulla Sadra, essence is the overall picture of reality or objects that exist in the mind; and existence is the objective reality outside the mind. (3) The concepts of essence and existence according to Ibn Arabi and Mulla Sadra have common ground in defining the concepts of essence and existence and also in comparing the concepts of essence and existence.